IgA Vasculitis and C3 Glomerulonephritis: One Patient... Various Autoimmune Diseases - Gaudêncio, Ana Margarida Pedro Antunes Ferreira; Lameiras, Ana Catarina; Mendonça, Teresa (Gazeta Médica, 2022)
Leucocytoclastic vasculitis refers to a small vessel vasculitis caused by immune complexes, infections and medications. IgA or IgM/IgG immune complexes can be found in direct immunofluorescence studies suggesting specific forms of leucocytoclastic vasculitis. Some authors suggested that IgA vasculitis and IgA nephropathy were two clinical mani- festations of the same disease. From a histological point of view, it is not possible to distinguish a glomerulonephritis as part of an IgA vasculitis from an IgA nephropathy. The authors present a case of a 50-year-old woman diagnosed with vitiligo ad immune thrombocytopenic purpura (ITP). ITP was diagnosed 2 years before the present case. She presented to the autoimmune diseases’ appointment with a pruriginous rash of the lower extremities over the last 3 months. Skin biopsy was suggestive of leukocytoclastic vasculitis, revealing deposits of C3, IgG (less intensity) and IgA. IgA vasculitis was then assumed. After a few weeks, she kept peripheral edema, but an increasing decline in renal function was detected. Therefore, a renal biopsy was performed, which revealed endocapilar proliferative glomerulonephritis and predominantly C3 mesangial deposits, with IgA and vestigial IgM. These results were compatible with a C3 glomerulonephritis. The patient was started on systemic steroid treatment with prednisolone 1 mg/kg/day and ramipril 2.5 mg/day with progressive normalization of renal function. With this case, the authors emphasize the possibility that all these manifestations could be part of the same disease spectrum, but also, the importance of complement activation. So, this case may constitute additional evidence of the complement activation in pathogenesis of this vasculitis, however, further investigation is need, particularly to understand C3 glomerulonephritis, a rare kidney disease.